Physical properties of halloysite nanotubes-polyvinyl alcohol nanocomposites using malonic acid crosslinked - Gaaz, Tayser Sumer; Hussein, Emad Kamil; Al-Amiery, Ahmed A. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Halloysite nanotubes (HNTs) based nanocomposites were produced by blending individualized HNTs dispersion with polyvinyl alcohol (PVA). Several sequential separation techniques were applied to obtain stable individualized HNTs dispersion. The preparation of PVA-crosslinked-HNTs nanocomposite has not been developed and, to the best of our knowledge, there was no published report indicating the use of neither dispersion nor crosslinker agent. In addition, PVA was crosslinked using the crosslinker malonic acid (MA) and sulfuric acid as a catalyst. This individualization increases the mechanical and thermal properties of HNTs-PVA nanocomposites. As a side result, crosslinking was employed to make PVA water-insoluble and hence to become more useful in biomedical applications. Examination of the nanocomposites indicated that HNTs were uniformly dispersed in both PVA as well as crosslinked PVA. These nanocomposites could be composted easily and hence would be good candidates to\replace some of today’s traditional non-biodegradable plastics that end up in landfills.